Switzerland : Report on Observance of Standards and Codes; Fiscal Transparency Module. (IMF Staff Country Reports; Country Report, 2009)
This paper focuses on the observance of standards and codes on fiscal transparency for Switzerland. The assessment reveals that the fiscal role of the executive and legislative branches of government, and the legal framework for the management of federal public finances, are clearly defined. The federal budget process is governed by a precise legal framework. A coherent medium-term fiscal framework provides a clear context for budget decisions. The accuracy of macroeconomic forecasts compares favorably with private sector counterparts. There are some areas, however, where further measures could be considered.